Noah's curse: the biblical justification of American slavery - Haynes, Stephen R. (Religion in America series, 2002)
In Noah's Curse, Stephen Haynes explores the historical context of slavery. The author identifies the manner in which the great and good interpreted the story in Genesis to provide free labour and a scriptural justification for the Black Holocaust